Bankruptcy analysis using altman z-score model in retail trading company listed in Indonesia stock exchange - Ramadona Simbolon; Sri Elviani (Proceedings of AICS - Social Sciences, 2017)
The purpose of this study was to bankruptcy prediction in trading retail companies listed in Indonesian Stock Exchange. The population of this study is a retail company listed on the Indonesia Stock Exchange, which amounted to 22 companies. The research samples were 19 companies, selected using purposive sampling method. This study uses secondary data that collected from Indonesian Stock Exchange website in the form of audited financial statements for years 2015 and 2016. We used Altman Z Score for data analysis. This study find that 3 firms in 2016 and 2015 are always on the bankruptcy classification with z score of less than 1.8, so the findings of this study can be useful for managers and shareholders in financial decision-making to take steps financial and business strategic and for governments to work out solutions to prevent bankruptcy by boosting economic growth and suppressing inflation rates to increase public purchasing power. This study also find 8 firms are always in a non-bankrupt or healthy classification with an Altman score of z score greater than 2.9, so, these findings can be useful for managers and shareholders to make financial decisions, by looking for investment options to make available funds can be utilized and not just focus on retail companies only.